Parental Drought-Priming Enhances Tolerance to Post-anthesis Drought in Offspring of Wheat - Wang, Xiulin; Zhang, Xiaxiang; Chen, Jing; Wang, Xiao; Cai, Jian; Zhou, Qin; Dai, Tingbo; Cao, Weixing; Jiang, Dong (Frontiers in Plant Science, 2018)
Drought is the major abiotic stress that decreases plant water status, inhibits photosynthesis, induces oxidative stress, restricts growth and finally lead to the reduction of wheat yield. It has been proven that drought priming during vegetative growth stage could enhance tolerance to drought stress at grain filling in wheat. However, whether drought priming imposed at grain filling in parental plants could induce drought tolerance in the offspring is not known. In this study, drought priming was successively applied in the first, the second and the third generation of wheat to obtain the plants of T1 (primed for one generation), T2 (primed for two generations), T3 (primed for three generations). The differently primed plants were then subjected to drought stress during grain filling in the fourth generation. Under drought stress, the parentally primed (T1D, T2D, T3D) plants, disregarding the number of generations, showed higher grain yield, leaf photosynthetic rate and antioxidant capacity as well as lower O2.- release rate and contents of H2O2 and MDA than the non-primed (T0D) plants, suggesting that drought priming induced the transgenerational stress tolerance to drought stress. Moreover, the parentally primed plants showed higher leaf water status, which may result from the higher contents of proline and glycine betaine, and higher activities of Δ1-pyrroline-5-carboxylate synthetase (P5CS) and betaine aldehyde dehydrogenase (BADH), compared with the non-primed plants under drought stress. In addition, there was no significant difference among three generations under drought, and the drought priming in parental generations did not affect the grain yield of the offspring plants under control condition. Collectively, the enhanced accumulation of proline and glycine betaine in the parentally primed plants could have played critical roles in parental priming induced tolerance to drought stress. This research provided a potential approach to improve drought tolerance of offspring plants by priming parental plants.